Utilizing the Aquatic Exercises Approach Intervention (AEAI) Program for a Filipino Adolescent with Autism - Dimarucut, Alberto L.; Lozada, Keona Marie V.; Castro, Camille B.; Papa , Emmanuel Liberato V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Acquiring swimming skills is critical for individuals with autism spectrum disorder (ASD) since drowning is one of the leading causes of death for the ASD community (National Autism Association, 2011). A qualitative content analysis research design was used to investigate the effect of aquatic exercises approach on the development of swimming skills needed by a student with ASD to swim independently. The study used a 10-day Aquatic Exercises Approach Intervention (AEAI) program. Also, the Swimming and Water Independence Measure (SWIM) test consists of eleven swimming skills, developed by the Halliwick's Association of Swimming Therapy, was used for the pre-test and post-test. A detailed description of progress was created for each of the swimming skills. The study showed that the AEAI program showed significant improvements in ten of the aquatic skills. The only exception was the Breath Control skill wherein the student maintained his score in both assessments. The findings showed that the AEAI program can help a student with ASD acquiring the swimming skills needed to swim independently. However, future lessons may include more than one student or make changes to the program adaptable to diverse groups.